Modern Therapy of Viral Hepatitis - Abdulloev Mukhriddin Ziyodulloevich (Zien Journals, 2023)
Viral hepatitis (VH) is a large group of diseases that differ in etiology, epidemiology, and clinical presentation with predominant liver damage. Currently, the following independent forms of VG are known, which are usually denoted by letters of the Latin alphabet: A, B, C, D, E, G, TTV. The greatest importance for practical health care is represented by hepatitis with parenteral (or hemocontact) infection and, above all, hepatitis caused by viruses B, C, D. This is due to the fact that when infected with these viruses, the course of the disease is usually more severe than with hepatitis A and E, lightning-fast (malignant) infections are possible
Keywords: Etiotropic treatment; hepatitis, clinic; hepatitis, clini